Metabolic relay gene of aphid and primary symbiont as RNAi target loci for aphid control - Li, Qian; Cheng, Yu; Fan, Jia; Chen, Julian (Frontiers in Plant Science, 2023)
Introduction Aphids form a stable and mutually beneficial relationship with their primary symbiont Buchnera aphidicola, which play an important role in providing the missing nutrients to the host aphid. Based on the genome sequence of wheat aphid Siotobion miscanthi and its primary symbiont Buchnera that we obtained in our previously study, we identified a metabolic relay gene, ilvA, involved in the isoleucine synthesis pathway between aphids and Buchnera. Method In this study, we identified the location and sequence structure of ilvA gene in aphid genome, the expression level in different instars and tissues of aphids, and the effect of reducing ilvA expression on the growth and development of aphids by bioinformatics analysis, quantitative PCR, RNAi and bioassay experiments. Result Our study showed that ilvA was expressed at the highest level in the 2nd instar of the aphid, while the expression of this gene was significantly higher in the aphid bacteriocytes than in other tissues. Notably, this gene is localized on the aphid sex chromosome and remains highly conserved and collinearity across different aphid genomes. Knocking down the expression of ilvA reduced the aphid body weight and production. However, the indices of mortality decreased slightly, but were not significantly different, compared to the control. Discussion The results show that the relay genes between aphids and their symbionts in the metabolism of essential nutrients have potential roles in the growth and development of aphids, meanwhile, providing target loci and new ideas for RNAi-based aphid green control strategies.